2011
DOI: 10.1089/mdr.2010.0098
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and Dominance of CTX-M-15 Extended Spectrum Beta-Lactamase Among Escherichia coli Isolates from Children

Abstract: Of forty-seven extended-spectrum cephalosporin-resistant Escherichia coli isolates, collected from children at the Children's Hospital in 2006 (Tunis, Tunisia), we analyzed 32 isolates that were genotypically different by enterobacterial repetitive intergenic consensus -polymerase chain reaction. For all isolates, the double-disk diffusion test revealed synergy between clavulanate and cefotaxime and/or ceftazidime, suggesting the production of extended-spectrum beta-lactamases. Polymerase chain reaction experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…In Tunisia, it has been reported that CTX-M-15 is the main type of ESBL in clinical E. coli isolates recovered in hospitals [7][8][9]23], and CTX-M-1 is the most frequent type among food E. coli isolates [3,4]. These data may suggest the potential food origin of the isolates recovered in the healthy human population, and the potential implication of the food chain in the transmission processes.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In Tunisia, it has been reported that CTX-M-15 is the main type of ESBL in clinical E. coli isolates recovered in hospitals [7][8][9]23], and CTX-M-1 is the most frequent type among food E. coli isolates [3,4]. These data may suggest the potential food origin of the isolates recovered in the healthy human population, and the potential implication of the food chain in the transmission processes.…”
Section: Discussionmentioning
confidence: 90%
“…Similarities between the type of ESBLs and plasmids detected in E. coli isolates from humans, animals and food have suggested the potential transference of these ESBL genes from animals to humans, most likely through the food chain [6]. CTX-M-15 is the most frequent type of ESBL detected among clinical E. coli isolates in Tunisia [7][8][9]. However, this type of beta-lactamase has not been detected in food isolates in this country, in which the CTX-M-1 variant was frequently identified [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In Tunisia, class A and D ESBLs, pAmpC, and carbapenemases were present, and the prevalence ranged from 11.7 to 77.8% in hospitals and was 0.7 and 7.3% in two communities (3451). …”
Section: Resultsmentioning
confidence: 99%
“…The blaCTX-M-15 ESBL gene is considered to be the most prevalent ESBL worldwide, as it is found in a Tunisian study analyzed 32 ESBL E. coli isolates collected during a 10-month period, which reported the emergence of CTX-M-15 in 97% (31/32) of isolates; and 81% (26/32) also harbored TEM-1 (Réjiba et al, 2011).…”
Section: Discussionmentioning
confidence: 99%